INFLUENCE OF NETWORK CAPACITY AND INFORMATION AND KNOWLEDGE SHARING ON OPEN INNOVATION - Mannes, Silvana; Beuren, Ilse Maria (Advances in Scientific and Applied Accounting, 2021)
Objective: This article analyzes the influence of network capacity and information and knowledge sharing on open innovation in startups related to large companies. Method: A survey was carried out with managers of startups ranked on the 100 Open Startups platform. The survey population comprises 324 startups and the sample the 144 valid responses. For data analysis, structural equation modeling by partial least squares was applied. Results: The results revealed a direct and significant influence between information sharing and open innovation, as well as between knowledge sharing and open innovation. Although no direct influence of network capacity on open innovation was found, mediation of information and knowledge sharing was observed in this relationship, which indicates that network capacity can be an important antecedent and indirectly impacts the performance of open innovation. It is concluded that the investigated variables are important drivers of open innovation performance, in order to reduce risks and bring benefits to startups in interorganizational relationships. Contributions: The results contribute to the literature by revealing the mediating effect of information and knowledge sharing in the relationship between network capacity and open innovation performance, an advance in the understanding of shared resources. They also have practical and social implications, as they provide information about interorganizational relationships. It is expected that the findings can help managers in conducting the relationship, with the purpose of reducing asymmetries between those involved and directing towards a beneficial relationship for both parties.